Systematic revision of Calligrapha s. str. Chevrolat (Coleoptera: Chrysomelidae, Chrysomelinae) - Gómez-Zurita, Jesús (Zootaxa, 2021)
In this work, the Chrysomelinae leaf beetle subgenus Calligrapha s. str. Chevrolat, 1836 is revised, offering redescriptions and keys for identification of twelve species currently considered in this group, allied to the South American species Calligrapha polyspila (Germar, 1821), the generic type of Calligrapha. The current species count results from important taxonomic changes. These include reversing a long-held synonymy, resurrecting the name Calligrapha mexicana Stål, 1859 stat. rev. for a species that is different from Chrysomela serpentina Rogers, 1856; upgrading the status of Polyspila serpentina var. discrepans Achard, 1923 to Calligrapha discrepans (Achard) stat. rev.; and formally proposing a number of new synonymies for several species, including: (1) Calligrapha discrepans (Achard) (= Calligrapha serpentina ssp. temaxensis Bechyné, 1952 syn. nov.); (2) Calligrapha fulvipes (Gistel, 1848) (= Calligrapha bajula Stål, 1860 syn. nov.; = Calligrapha nupta Stål, 1859 syn. nov.; = C. sponsa Stål, 1859 syn. nov.); and (3) Calligrapha polyspila (Germar) (= Polyspila polyspila var. bilineolata Achard, 1923 syn. nov.; = Polyspila polyspila var. plagata Achard, 1923 syn. nov.).